2019
DOI: 10.1097/aln.0000000000002729
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Delirium and Postoperative Cognitive Dysfunction

Abstract: Editor’s Perspective What We Already Know about This Topic What This Article Tells Us That Is New Background Postoperative delirium and postoperative cognitive dysfunction share risk factors and may co-occur, but their relationship is not well established. The primary goals of this study were to describe the prevalence of posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
145
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(173 citation statements)
references
References 61 publications
5
145
0
2
Order By: Relevance
“…A total of 110 adults were recruited in this study (Figure 1). Patients were excluded if they: (Daiello et al, 2019) had a past medical history of neurological disease such as delirium, schizophrenia, dementia, or stroke [with regard to dementia, it was screened if Mini Mental State Examination (MMSE) scores of ≤ 17 for illiterate patients, ≤ 20 for patients with 1-6 years of education, or ≤ 24 for patients with 7 or more years of education] (Li et al, 2016;Vutskits and Xie, 2016) were unable to read or write or cooperate; (Eckenhoff et al, 2020) had a history of drug or alcohol abuse. Eighty participants (15 POD vs. 65 Non-POD) completed the study.…”
Section: Patients and Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 110 adults were recruited in this study (Figure 1). Patients were excluded if they: (Daiello et al, 2019) had a past medical history of neurological disease such as delirium, schizophrenia, dementia, or stroke [with regard to dementia, it was screened if Mini Mental State Examination (MMSE) scores of ≤ 17 for illiterate patients, ≤ 20 for patients with 1-6 years of education, or ≤ 24 for patients with 7 or more years of education] (Li et al, 2016;Vutskits and Xie, 2016) were unable to read or write or cooperate; (Eckenhoff et al, 2020) had a history of drug or alcohol abuse. Eighty participants (15 POD vs. 65 Non-POD) completed the study.…”
Section: Patients and Settingmentioning
confidence: 99%
“…Patients over 65 years of age are the largest consumers of procedural care, and postoperative delirium (POD) is one of the most common complications experienced by elderly patients during the postoperative period (Daiello et al, 2019). POD is an acute neuropsychiatric syndrome occurring in the hours to days after anesthesia and surgery (Vutskits and Xie, 2016), which can elicit durable deficits in executive function, memory, attention, and other cognitive domains (Eckenhoff et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For patients infected with hepatitis B or female patients receiving lumbar plexus blocks and sciatic nerve blocks, the authors recommended that combined ultrasound and nerve stimulator guidance should be used to improve the safety, and the use of ultrasound did not improve the quality of deep nerve block [22]. In this study be- [23]. In the present study with centenary patients, the incidence of delirium in the immediate postoperative period was 11.4%.…”
Section: Parameters Psoas Groupmentioning
confidence: 49%
“…5 Patients, especially elderly patients, suffered cognitive decline after many kinds of surgery, but because of differences in assessment tools and methods, the reported incidence of POCD varied greatly. Following the 2018 recommended change to PND, when the diagnosis process and method were given, 2 Daiello et al 6 found that Hu Z. et al: Glymphatic system and PND Explor Res Hypothesis Med postoperative delirium and postoperative cognitive dysfunction may be distinct manifestations of perioperative neurocognitive deficits.…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%